2020
DOI: 10.1002/bdr2.1703
|View full text |Cite
|
Sign up to set email alerts
|

Maternal risk factors for gastroschisis: A population‐based case–control study

Abstract: BackgroundGastroschisis is an open abdominal wall defect with low mortality but significant morbidity. The prevalence has been increasing worldwide for the past decades. Several risk factors for gastroschisis have been identified, but no clear reason for increasing prevalence has been found. In our study, we aimed to assess and identify maternal risk factors for gastroschisis.MethodsIn our nationwide register‐based case–control study, we identified all gastroschisis cases in the Finnish Register of Congenital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…These include young maternal age, rural environment, cigarette smoking, low socioeconomic status and low maternal body mass index (BMI). 8,13,14 However, the prevalence of several risk factors stands juxtaposed with the increasing rate of gastroschisis. For example, BMI among reproductive aged women has been increasing, a trend that is expected to continue.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…These include young maternal age, rural environment, cigarette smoking, low socioeconomic status and low maternal body mass index (BMI). 8,13,14 However, the prevalence of several risk factors stands juxtaposed with the increasing rate of gastroschisis. For example, BMI among reproductive aged women has been increasing, a trend that is expected to continue.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…S3 Table gives the method of ascertainment of maternal diabetes of the included studies. Of the 59 studies included, there were 27 studies from the European region (United Kingdom [ 26 30 ], Finland [ 31 , 32 ], Sweden [ 10 , 33 37 ], Denmark [ 10 , 28 , 35 , 38 , 39 ], Norway [ 6 , 28 , 40 , 41 ], Hungary [ 7 , 42 45 ], Germany [ 28 , 46 ], Netherlands [ 28 ], Belgium [ 28 ], Wales [ 28 , 30 ], Ireland [ 28 , 30 ], Switzerland [ 28 ], France [ 28 , 47 ], Italy [ 28 , 48 , 49 ], Spain [ 28 ], Portugal [ 28 ], and Malta [ 28 ]), 25 studies from North/South America (United States [ 4 , 5 , 11 , 12 , 14 , 50 – 57 ], Canada [ 50 , 58 68 ], and Brazil [ 69 ]), and 7 studies from the Asian-Pacific region (China [ 70 72 ...…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained, in which the cut-off criterion for a maternal age of 25 years is adopted, are consistent with the results of studies by other researchers. 26,29 Anderson et al clearly indicate that the probability of defect occurrence decreases with maternal age. 17 Some authors observed a statistically significant frequency for the development of the abdominal wall defect in new-borns of mothers under 20 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that primiparity is a statistically significant risk factor for gastroschisis. 29 The highest risk of giving birth to an infant with gastroschisis was demonstrated for primiparas. This is confirmed by the current study, i.e.…”
Section: Discussionmentioning
confidence: 99%